Voices from the Past. Rearranging Values in Times of Crisis: The Example of North Indian Vaishnava Hagiographies. (January 2020) - Rousseva-Sokolova, Galina
This article is focussed on the study of a particular case of shift in religious values embodied in two seventeenth-century North Indian compilations of hagiographical narratives, elaborated within the religious community of Vallabhacharya, namely the collections of the 84 and 252 Vaishnava saints. The sect is presented against the backdrop of the mosaic-shaped Hindu landscape, where new ideas about sainthood and merit had come to challenge the established hierarchies and prevalent practices. The hagiographies, as a typical example of the 'story with a message' genre, bring down the lofty theological concepts, expounded in Sanskrit, to down-to-earth examples, voiced in everyday language, thus functioning as a practical guidance for followers of the sect. The article deconstructs the way narratives negotiate the establishing of a new religious value— bhakti —while addressing, at the same time, the devotees' more traditional concerns, pertaining to the well-being of the forefathers, ritual purity or the concept of salvation, and promoting to them the lifestyle of economically engaged householders against the withdrawal of renouncement.